Effect of Papaya Seed on Mortality and Midgut Histopathology in Aedes aegypti Larvaes - Agustini, Cynthia; Hasmiwati, Hasmiwati; Afriwardi (Frontiers on Healthcare Research, 2025)
Background: Indonesia is an endemic region for Dengue infection. The World Health Organization (WHO) reported Dengue as one of the top ten global health threats in 2020. Dengue is a viral infection transmitted primarily by the Aedes aegypti mosquito, causing Dengue Fever and Dengue Hemorrhagic Fever. Temephos 1.25% has been the WHO recommended standard larvicide. However, prolonged use and continuously increasing doses may result in resistance and toxicity, posing risks to the environment and human health. This necessitates the discovery of alternative larvicides that are effective in killing larvae with minimal side effects, particularly those derived from natural materials. Methods: This research intends to illustrate the impact of papaya seed extract on the death rate of larvae and the histopathological changes in the midgut of Ae. aegypti larvae. A genuine experimental framework featuring a control group with only post-testing was utilized for this investigation. The sample comprised 750 Ae. aegypti larvae, which were categorized into six groups: one negative control group (aquades), one positive control group (temephos 1. 25%), and four treatment groups using papaya seed extract at varying concentrations of 2 mg/ml (P1), 2. 5 mg/ml (P2), 3 mg/ml (P3), and 3. 5 mg/ml (P4). Results: The results showed that all larvaes died within 24 hours in the positive control, P1, P2, P3, and P4 groups. Probit analysis of papaya seed extract revealed LC50 at 2.599 mg/ml and LC90 at 4.776 mg/ml after 8 hours of exposure. Conclusion: This study concludes that papaya seed extract affects larval mortality and midgut histopathology alterations in Ae.aegypti larvae. These findings indicate that papaya seed extract holds great potential as a natural and environmentally safe as alternative larvicide to disrupt the development of dengue fever vectors.